1982
DOI: 10.1128/jb.150.2.916-924.1982
|View full text |Cite
|
Sign up to set email alerts
|

Roles of cell surface components of Escherichia coli K-12 in bacteriophage T4 infection: interaction of tail core with phospholipids

Abstract: The cell surface of Escherichia coli K-12, reconstituted from the OmpC protein, lipopolysaccharide, and the peptidoglycan layer, was active as a receptor for phage T4, resulting in the contraction of the tail sheath and the penetration of the core through the cell surface (Furukawa et al., J. Bacteriol. 140:1071--1080, 1979). In the present work the process of DNA ejection from the contracted T4 phage particle was studied. Contracted phage particles were adsorbed to phospholipid liposomes by the core tip. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…In fact, treatment of the virion with urea causes sheath contraction, but the phage retains the entire DNA. It has been shown that the phage with a contracted sheath due to urea treatment can infect host spheroplasts (Furukawa and Mizushima 1982;Furukawa et al 1979Furukawa et al , 1983.…”
Section: Formation Of the Contractile Tail Sheathmentioning
confidence: 99%
“…In fact, treatment of the virion with urea causes sheath contraction, but the phage retains the entire DNA. It has been shown that the phage with a contracted sheath due to urea treatment can infect host spheroplasts (Furukawa and Mizushima 1982;Furukawa et al 1979Furukawa et al , 1983.…”
Section: Formation Of the Contractile Tail Sheathmentioning
confidence: 99%
“…Lipid components of membranes seem to play a significant role in the viral infection process of eucaryotic and procaryotic cells (18,23), and the activity of bacteriophage receptor proteins is strongly enhanced in the presence of lipids and the lipid portion of lipopolysaccharides (15,17,36). Furthermore, phosphatidylglycerol (PG) and cardiolipin (CL) in reconstituted membrane vesicles have been implicated to trigger DNA release from the T4 capsid (13).…”
mentioning
confidence: 99%
“…The lipoprotein-bearing peptidoglycan layer that underlies the outer membrane allows the OmpC protein and lipopolysaccharide to assemble widely on its surface so that the receptor complex can interact with the individual distal ends of the long tail fibers of a single phage particle (9). It also serves as a rigid support for the outer membrane to help the penetration of the phage core through the flexible outer membrane (8). The core tip that has penetrated the cell surface interacts with a phospholipid bilayer, representative of the cytoplasmic membrane, and the interaction induces the ejection of phage DNA through the core (8).…”
mentioning
confidence: 99%
“…It also serves as a rigid support for the outer membrane to help the penetration of the phage core through the flexible outer membrane (8). The core tip that has penetrated the cell surface interacts with a phospholipid bilayer, representative of the cytoplasmic membrane, and the interaction induces the ejection of phage DNA through the core (8). However, the DNA molecule thus ejected is not incorporated into the liposomes.…”
mentioning
confidence: 99%